Students' Attitudes toward Immigrants: An Analysis of ICCS Data - Špela Javornik (International School for Social and Business Studies, 2023)
Purpose: This study investigates changes in students' attitudes toward immigrants among 14-year-old students in Slovenia, between the International Civic and Citizenship Education Study (ICCS) cycles of 2009 and 2016. Additionally, it explores the relationship between civic knowledge and attitudes toward immigrants. Study design/methodology/approach: The study performed descriptive statistics and further linear regression analysis to investigate the relationship between civic knowledge and students' attitudes toward immigrants. Findings: The results show that attitudes toward immigrants have become slightly more positive between the two cycles in Slovenia, but the differences are not statistically significant. Civic knowledge is positively related to attitudes toward immigrants in both cycles. These findings are consistent with previous studies, highlighting the importance of education in promoting positive attitudes toward immigrants and the need for continuous evaluation of educational policies and practices to improve attitudes toward immigrants in Slovenia and beyond. Originality/value: The originality and value of this study lie in its focus on Slovenian students' attitudes toward immigrants and their relationship with civic knowledge, by analyzing data from two ICCS cycles.